Energy characteristics of thermoelectric converters powered by human body heat - Kobylianskyi, R.R. (Journal of Thermoelectricity, 2022)
The paper presents a three-dimensional physical model, analytical description and results of computer simulation of thermoelectric converters placed on the surface of the human body. The optimal properties of thermoelectric converters are determined, at which the maximum values ​​of electrical power Wmax and efficiency are achieved in the resting state and during physical stress of the human body.